Seasonal and Interannual Variability of Water Exchange in the Strait of Istanbul - ALTIOK, Η.; KAYIŞOĞLU, M. (Mediterranean Marine Science, 2015)
Temperature and salinity distribution and volume fluxes through the Strait of Istanbul were analysed using long-term monthly time series of temperature-salinity (1996-2010) and current profiles (1999-2010) collected at both ends of the strait. While annual cycle of the upper layer temperature, with minima in February and maxima in August, reflects the influence of air temperature with a near monthly phase shift, annual cycle of the upper layer salinity, with lowest values observed between April to September, is mostly affected by river discharge into the Western Black Sea. The seasonal variations of the lower layer temperature and salinity in the Strait of Istanbul are mostly influenced by flow blockages. Inversely proportional upper and lower layer volume fluxes indicate strong seasonal variations with minimum and maximum values in April and October, respectively. Annual average upper and lower layer volume fluxes calculated from the high resolution dataset are 404 km3 y-1 and 250 km3 y-1 at the north end, and 430 km3 y-1 and 245 km3 y-1 at the south end of the strait, respectively.